A Familial Cluster of Infection Associated With the 2019 Novel Coronavirus Indicating Possible Person-to-Person Transmission During the Incubation Period. (18th February 2020) - Yu, Ping; Zhu, Jiang; Zhang, Zhengdong; Han, Yingjun
Abstract: An ongoing outbreak of pneumonia associated with 2019 novel coronavirus was reported in China. It is unclear whether the virus is infective exists during the incubation period, although person-to-person transmission has been reported elsewhere. We report the epidemiological features of a familial cluster of 4 patients in Shanghai, including an 88-year-old man with limited mobility who was exposed only to asymptomatic family members whose symptoms developed later. The epidemiological evidence has shown possible transmission of 2019 novel coronavirus during the incubation period. Abstract : In a familial cluster of four 2019 novel coronavirus (nCoV) cases in Shanghai, the first patient was exposed only to asymptomatic family members, whose symptoms developed later. These findings suggest possible transmission of 2019-nCoV during the incubation period.